2008
DOI: 10.1038/nm1766
|View full text |Cite
|
Sign up to set email alerts
|

Activation of c-Kit in dendritic cells regulates T helper cell differentiation and allergic asthma

Abstract: Dendritic cells (DCs) are integral to differentiation of T helper cells into Th1, Th2 and Th17

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
221
1
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 190 publications
(235 citation statements)
references
References 50 publications
10
221
1
2
Order By: Relevance
“…Intravenous or intracranial injection of BMMCs has been recently found to restore the pool of meningeal MCs in Kit W/W-v mice, leading to the recovery of a WT-like disease course and to the rescue of neutrophil infiltration in the CNS. 20 In our system, although detecting scattered MCs in Kit þ / þ mice in the context of the reticulum formed by the arachnoid, the subdural neurothelium, and the dura mater, in line with previous observations, 29 we could not find MCs populating the [45][46][47] in Kit W-sh/W-sh mice, without finding any difference, according to previous data. 29 However, we cannot exclude that DC-expressed c-Kit has some role on immunization, as demonstrated in a model of allergic asthma, in which Ag/adjuvant exposure induced on DCs the expression of both c-Kit and its ligand, promoting Th2 and Th17 responses.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Intravenous or intracranial injection of BMMCs has been recently found to restore the pool of meningeal MCs in Kit W/W-v mice, leading to the recovery of a WT-like disease course and to the rescue of neutrophil infiltration in the CNS. 20 In our system, although detecting scattered MCs in Kit þ / þ mice in the context of the reticulum formed by the arachnoid, the subdural neurothelium, and the dura mater, in line with previous observations, 29 we could not find MCs populating the [45][46][47] in Kit W-sh/W-sh mice, without finding any difference, according to previous data. 29 However, we cannot exclude that DC-expressed c-Kit has some role on immunization, as demonstrated in a model of allergic asthma, in which Ag/adjuvant exposure induced on DCs the expression of both c-Kit and its ligand, promoting Th2 and Th17 responses.…”
Section: Discussionsupporting
confidence: 92%
“…Beside MCs, other cells of the immune system may express c-Kit at variable levels and under different circumstances, 44 such as dendritic cells (DCs). 45 C-Kit pharmacological inhibition fosters a productive cross-talk between DCs and natural killer (NK) cells 46 and promotes the differentiation of a DC subset endowed with cytotoxic ability and IFN-g competence. 47 However, as previously reported, 29 we did not observe any difference between naive Kit W-sh/W-sh and Kit þ / þ mice in NK or DC frequency in the spleen (Supplementary Figure S6).…”
Section: Alterations In the Granulocytementioning
confidence: 99%
“…Under these conditions, lung DC receive proper maturation stimuli and release cytokines and costimulatory molecules that become the most important factors in determining the outcome of the cellular immune response. Many groups [41][42][43] have suggested that lung DC have an intrinsic bias to promote Th2 responses, most likely via production of IL-6, but it remains unclear whether this Th2 susceptibility is linked to a particular cDC subset. Recently however, c-Kit expression identified a Th2-prone subset of lung DC [43].…”
Section: Antigen Presentation and T-cell Polarizationmentioning
confidence: 99%
“…Many groups [41][42][43] have suggested that lung DC have an intrinsic bias to promote Th2 responses, most likely via production of IL-6, but it remains unclear whether this Th2 susceptibility is linked to a particular cDC subset. Recently however, c-Kit expression identified a Th2-prone subset of lung DC [43]. In our view, any lung DC can induce CTL responses, and Th1, Th2 or Th17 Th effector responses depending on the type and strength of inciting stimulus, with only minor bias due to lineage or surface markers.…”
Section: Antigen Presentation and T-cell Polarizationmentioning
confidence: 99%
See 1 more Smart Citation